Taiwan Straits crisis in Asia and the role of the U.S. Navy - Elleman, Bruce A. 1959- (Global flashpoints, 2015)
In this book, Elleman surveys the situation that has led to the current tensions between China and Taiwan. Simply written and cogently argued, it is the ideal source for military personnel, diplomats, and scholars and student of the modern Far East.